Peningkatan Layanan di Laboratorium dengan Aplikasi POLAR (Portal Layanan Laboratorium Berbasis Mobile) - R Rahmawati; Krisna Eka Pratama (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Laboratories function as essential academic support units for knowledge acquisition in the implementation of education, research, and community service; therefore, they require effective management and utilization. To enhance integrated laboratory services and management, the POLAR Application (Mobile-Based Laboratory Service Portal) was developed as an innovative solution. This application aims to improve the quality of integrated laboratory services by digitizing service data. Accessible features include the Integrated Chemical Management System (SIBAKI) and the Digitalization of Laboratory Instruments (DILab) utilizing QR Code technology. The POLAR Application is available for download via the Google Play Store and App Store and currently serves over 1,000 active users across various countries, including Indonesia, the United States, France, India, and Japan. The development process involved several stages: conceptualization and feature analysis, database and application structure design, frontend and backend coding, periodic system testing and debugging, and finally, the User Acceptance Test (UAT). This service improvement provides users with a modern, transparent system that synergizes directly with the community. Feedback results indicate that 100% of respondents are now aware of the available laboratory services. This demonstrates that the optimization process has successfully achieved efficiency, making the retrieval of information regarding laboratory services significantly faster and easier.